1980
DOI: 10.1002/em.2860020307
|View full text |Cite
|
Sign up to set email alerts
|

Absence of arsenite mutagenicity in E coli and chinese hamster cells

Abstract: Because exposure to compounds of arsenic has been implicated as a cause of cancer, an investigation of the mutagenicity of sodium aresenite in E coli and in Chinese hamster cells was performed. In the E coli system, Trp + revertants were not induced by arsenite in a variety of experimental protocols including spot tests, treat and plate protocols, and fluctuation tests. The mutator effect of a tif-1 strain was partially blocked by arsenite. Arsenite did not cause the induction of lambda prophage. In Chinese ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…1, where the surviving fractions, after either a 1-or a 5-day continuous exposure, are plotted against drug concentration. The survival data fit well to a log-linear curve, and the lack of a shoulder in the dose-response curves is consistent with previous reports that arsenic inhibits DNA repair or recovery processes that normally act to produce a shoulder (15,30). The mean lethal doses, D o , defined as the concentrations that reduced survival to 0.37 (1͞e) in the log-linear portion of the curves for the 5-and 1-day treatments, were 1.3 and 1.7 g͞ml, respectively.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1, where the surviving fractions, after either a 1-or a 5-day continuous exposure, are plotted against drug concentration. The survival data fit well to a log-linear curve, and the lack of a shoulder in the dose-response curves is consistent with previous reports that arsenic inhibits DNA repair or recovery processes that normally act to produce a shoulder (15,30). The mean lethal doses, D o , defined as the concentrations that reduced survival to 0.37 (1͞e) in the log-linear portion of the curves for the 5-and 1-day treatments, were 1.3 and 1.7 g͞ml, respectively.…”
Section: Resultssupporting
confidence: 88%
“…The lack of suitable animal models necessitates reliance on in vitro studies to determine the cellular and molecular pathways involved. Previous genotoxic studies of arsenic have largely yielded negative findings for gene mutations but positive results for chromosomal aberrations (4,6,15,16). The failure of arsenic to induce gene mutations in mammalian cells has been taken as evidence that a nongenotoxic pathway is responsible for arsenic-induced cancer through either hypomethylation of DNA (32) or inhibition of DNA ligation (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the p53 mutation has been found in some As-associated bladder cancer, As fails to produce gene mutations at specific genetic loci in vitro (Rossman et al, 1980). Repeated injections of As and its compounds cannot definitely induce tumours in animal experiments (Chiang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although arsenic and arsenical compounds are toxic and induce morphological transformants in Syrian hamster embryo and C3H 10T1͞2 cells (12,13), they have been found to be inactive, as gene mutagens at the hypoxanthine guanine phosphoribosyl transferase (HPRT) and ouabain loci (12,14) and are only marginally active at the thymidine kinase locus of L5178 mouse lymphoma cells (15). In contrast, recent studies by Moore et al that use the latter assay have reported a much higher mutagenic response to arsenite under exposure conditions similar to those of the former study (16).…”
mentioning
confidence: 99%